1999
DOI: 10.1002/biof.5520100405
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of murine macrophage function by N‐acetylcysteine in a model of endotoxic shock

Abstract: In previous studies we have observed changes in several functions of peritoneal macrophages from BALB/c mice with irreversible endotoxic shock caused by intraperitoneal injection of E. coli lipopolysaccharide (LPS) (100 mg/kg), which were associated with a high production of superoxide anion. Since antioxidants, such as N-acetylcysteine (NAC), are free radical scavengers that improve the immune response, in the present work we have studied different functions of peritoneal macrophages from BALB/c mice sufferin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 36 publications
1
29
0
1
Order By: Relevance
“…␣TOC prevents membrane polyunsaturated fatty acids from undergoing lipid peroxidation, which leads to loss of membrane integrity (34). Of note, the doses of antioxidants that were effective in inhibiting LPS-induced cytokine production in the present experiments are similar to those previously reported to be effective in other cell types (11,35,36).…”
Section: Discussionsupporting
confidence: 89%
“…␣TOC prevents membrane polyunsaturated fatty acids from undergoing lipid peroxidation, which leads to loss of membrane integrity (34). Of note, the doses of antioxidants that were effective in inhibiting LPS-induced cytokine production in the present experiments are similar to those previously reported to be effective in other cell types (11,35,36).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, NAC results in increased NO release, leading to platelet inhibition [39] and vasodilatation of small blood vessels [40]. Several murine studies have demonstrated immunomodulating effects such as decreased leukocytes adherence [41,42,43] and decreased superoxide and tumor necrosis factor α production [44]. When given as pretreatment to endotoxic dogs, NAC resulted in improved global oxygen extraction and lower lactate levels [45,46].…”
Section: Resultsmentioning
confidence: 99%
“…GSH function is potentially enhanced by the administration of NAC, which has also itself an antioxidant and immunomodulatory activity [77][78][79][80][81][82]. Studies in humans demonstrated that the administration of NAC can significantly increase hepatosplanchnic blood flow attributed to the increase of cardiac index [83] and can augment neutrophil phagocytosis in patients diagnosed with sepsis, systemic inflammatory response syndrome (SIRS), or multiple trauma [84].…”
Section: N-acetylcysteine (Nac)mentioning
confidence: 99%